Circulating miR‐155, let‐7c, miR‐21, and PTEN levels in differential diagnosis and prognosis of idiopathic granulomatous mastitis and breast cancer. (17th September 2020) - Aksan, Hulya; Kundaktepe, Berrin Papila; Sayili, Ugurcan; Velidedeoglu, Mehmet; Simsek, Gonul; Koksal, Selcuk; Gelisgen, Remise; Yaylim, Ilhan; Uzun, Hafize
Abstract: This study investigates whether the circulating miR‐155, let‐7c, miR‐21, and PTEN levels to be used in the differential diagnosis of patients with idiopathic granulomatous mastitis (IGM) and breast cancer (BC). Forty‐five patients with BC, 50 patients with IGM, and 48 healthy volunteers were included in the study. Serum miR‐21 expression was significantly higher in BC (fold change = 2.42) and IGM group (fold change = 1.33) compared to control ( p  < .001). Serum miR‐155 and let‐7c expression levels were significantly lower in both groups compared to the control group ( p  < .001). miR‐21 expression in BC was significantly higher than IGM (fold change = 1.976; p  < .001). PTEN levels in BC were significantly higher than IGM ( p  < .001) and significantly lower than the control group ( p  < .001); the IGM group was significantly lower than the control group ( p  < .001). In addition to radiological data, serum miR‐21 and PTEN levels may be noninvasive biomarkers that can help differentiate IGM from BC. The results of the study will lead to future studies in the differential diagnosis of IGM and BC.